Advance Home Security System Using Arduino - Nagaraja Naika D. N; Jayachandra C; Thirumala Patil M (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This project introduces an advanced home security system using Arduino, designed to safeguard residential spaces with smart and cost-effective solutions. The system integrates PIR sensors for motion detection, ultrasonic sensors for intrusion monitoring, and a password-based access control for secure entry. A GSM module sends real-time SMS alerts to homeowners, while a buzzer and LCD display provide immediate local feedback. Compact, reliable, and energy-efficient, this system offers a practical alternative to conventional methods, enhancing safety and peace of mind. The project demonstrates how Arduino-based technology can provide efficient, affordable, and user-friendly security solutions.
Keywords: Arduino; Home Security; GSM Module; PIR Sensor; Ultrasonic Sensor; Password Access; Smart System